2006
DOI: 10.1097/00000542-200612000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Hypoxia Inducible Factor 1α by Isoflurane in Hep3B Cells

Abstract: Isoflurane can up-regulate HIF-1alpha and enhance HIF-1-responsive genes heme oxygenase 1, inducible nitric oxide synthase, and VEGF mRNA expression in Hep3B cells. The induction of HIF-1alpha by isoflurane does not involve protein degradation but depends on translation pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 51 publications
4
50
1
Order By: Relevance
“…Studies carried out by a number of laboratories have found that the predominant mechanism in this induction is an increase in HIF-1␣ protein translation via the PI3K pathway and mitogen-activated protein kinase pathway (32). Meanwhile, we recently have reported that volatile anesthetic isoflurane stimulates HIF-1␣ protein synthesis in the human hepatoma cell line Hep3B cells (29). So we focused first on the two pathways as a potential part of the intracellular signaling cascade activated by TNF␣/IL-4 in BEAS-2B cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies carried out by a number of laboratories have found that the predominant mechanism in this induction is an increase in HIF-1␣ protein translation via the PI3K pathway and mitogen-activated protein kinase pathway (32). Meanwhile, we recently have reported that volatile anesthetic isoflurane stimulates HIF-1␣ protein synthesis in the human hepatoma cell line Hep3B cells (29). So we focused first on the two pathways as a potential part of the intracellular signaling cascade activated by TNF␣/IL-4 in BEAS-2B cells.…”
Section: Discussionmentioning
confidence: 97%
“…The small interference RNA (siRNA) oligonucleotide for HIF-1␣ was designed as we described previously (29). Sense and antisense RNA strands for HIF-1␣-siRNA: 5=-UGU GAG UUC GCA UCU UGA UTT-3= and 5=-AUC AAG AUG CGA ACU CAC ATT-3=; for p65-siRNA: 5=-CUC AAG AUC UGC CGA GUA ATT -3= and 5=-UUA CUC GGC AGA UCU UGA GTT-3= were commercially synthesized (Genetimes Technology, Shanghai, China).…”
Section: Cells and Reagentsmentioning
confidence: 99%
“…The beneficial effect of isoflurane preconditioning may originate from its ability to induce endogenous cytoprotective pathways, such as the HO-1 pathway. Our group has previously reported that isoflurane induces HO-1 accumulation and that this effect is associated with the activation of the transcription factor HIF-1 in vitro [9,10] . Other groups have demonstrated the induction of HO-1 by isoflurane in liver tissue in vivo [11,12] .…”
Section: Introductionmentioning
confidence: 91%
“…Isoflurane pretreatment of the cells was performed in an airtight chamber, as previously described [9] . Briefly, cell dishes were kept in an airtight chamber that was housed within a water-jacketed incubator maintained at 37 °C.…”
Section: Isoflurane Exposure and Application Of Chemicalsmentioning
confidence: 99%
“…In hypoxic cells with accumulation of HIF-1 both halothane and propofol inhibit the HIF-1 accumulation [17,18]. It is reported that isoflurane and xenon enhance HIF-1 accumulation during hypoxia [19][20][21].…”
Section: Hif-1 Related Oxygen Sensingmentioning
confidence: 99%